Critérios de passa-falha na triagem auditiva neonatal universal por meio das emissões otoacústicas evocadas por estímulo transiente - Andrade, Isabela Freixo Côrtes de (2013)
Introduction: Transient Evoked Otoacoustic Emissions (TEOAE) is an usual tool in Newborn Hearing Screening programs (NHS). Pass-Fail parameters and criteria might be used in automated devices, and the choices for these criteria may change the sensitivity and specificity of the test applied to a newborn population. However, safe criteria must be carefully chosen in order to decrease false-positive and false-negative rates. Purpose: To analyze the outcomes of a NHS program using three different Pass-Fail criteria in an automated TEOAE device. Methods: The TEOAE results for 300 infants who were born at a philanthropic maternity in São Paulo were studied. The TEOAE recording was carried out using a portable automated device, and two different parameters were settled in the device. The first parameter, named broad band , was used in Study 1, and the second parameter was named- narrow band and it was used in Study 2. Both parameters allowed the analysis of three different Pass-Fail criteria: 3-band criterion - presence of responses in at least three different frequency bands, not necessarily consecutives; 2-band criterion - presence of responses in at least two frequency bands, not necessarily consecutives; narrow criterion - presence of responses using a narrow band filter between the frequencies of 1,600 and 3,200Hz. ABR was used as a gold stand test. Results: The comparison between the three different criteria showed that the 2-band criterion showed higher present responses (91.8%). However, this percentage was not statistically significant when compared to the narrow criterion (90.7%). On the other hand, there was a significant difference between the Pass-Fail percentages obtained with the 2-band and 3-band criteria (p<.001), with more frequent refer results for the 3-band . The three criteria presented high specificity (over 90%) and sensitivity (100%) values. No false-negative results were observed for all criteria, and the false-positive rates for the 3-band , 2- band and narrow criteria were, respectively: 0.10, 0.07, and 0.09. Conclusion: The three Pass-Fail criteria presented satisfactory statistical indices of sensitivity and specificity; however, based on the difference found between false-positive results, the 2-band criterion was the most efficient one to be used in NHS programs